(untitled) (Research, Society and Development, 2025)
Pineapple cultivation in Tarauacá, Acre, constitutes an agricultural practice relevant to the regional economy. This study aims to evaluate the agro-climatic suitability and climatic risks associated with cultivation in the área. Meteorological data were analyzed — air temperature, mean relative humidity, rainfall and Penman-Monteith reference evapotranspiration (ETo) — collected from the database of Xavier et al. (2022), covering 18 years (2001-2019). Available water capacity (28.28 mm) and readily available water (16.97 mm) of the soil served as central variables in modeling the normal and sequential water balance on a monthly basis. To measure the Water Need Satisfaction Index (ISNA), the relationship between crop Evapotranspiration (ETc) and monthly Eto was calculated. Precipitation revealed high seasonal variability, concentrated from October to May, with a dry period from June to September. The analysis reveals a favorable agroclimatic suitability for cultivation, with adequate temperatures and consistent annual rainfall; however, water deficits in the driest months suggest challenges for irrigation and water management practices.